Intra-host emergence of an enterovirus A71 variant with enhanced PSGL1 usage and neurovirulence - Liang Sun; Aloys Tijsma; Carmen Mirabelli; Jim Baggen; Maryam Wahedi; David Franco; Armando De Palma; Pieter Leyssen; Erik Verbeken; Frank J. M. van Kuppeveld; Johan Neyts; Hendrik Jan Thibaut (Emerging Microbes and Infections)
Enterovirus A71 (EV-A71) is one of the main causative agents of hand-foot-and-mouth disease and is occasionally associated with severe neurological complications. EV-A71 pathophysiology is poorly understood due to the lack of small animal models that robustly support viral replication in relevant organs/tissues. Here, we show that adult severe combined immune-deficient (SCID) mice can serve as an EV-A71 infection model to study neurotropic determinants and viral tropism. Mice inoculated intraperitoneally with an EV-A71 clinical isolate had an initial infection of the lung compartment, followed by neuroinvasion and infection of (motor)neurons, resulting in slowly progressing paralysis of the limbs. We identified a substitution (V135I) in the capsid protein VP2 as a key requirement for neurotropism. This substitution was also present in a mouse-adapted variant, obtained by passaging the clinical isolate in the brain of one-day-old mice, and induced exclusive neuropathology and rapid paralysis, confirming its role in neurotropism. Finally, we showed that this residue enhances the capacity of EV-A71 to use mouse PSGL1 for viral entry. Our data reveal that EV-A71 initially disseminates to the lung and identify viral and host determinants that define the neurotropic character of EV-A71, pointing to a hitherto understudied role of PSGL1 in EV-A71 tropism and neuropathology.